Pesantren and madrasa-based digital literacy practices: The case of the Darunnajah Islamic Boarding School, Jakarta - Deden Mauli Darajat; Iding Rosyidin; Dedi Fahrudin (Islamic Communication Journal, 2022)
Islamic boarding schools (pesantren) and madrasas have their own tradition of implementing digital literacy. This article aims to answer how digital literacy is practiced in Darunajah Islamic boarding schools? The method used in this study is a participatory method that involves research subjects in the research process. There are three digital literacy treatments given to subjects, namely content creator training, video making training, and Islamic journalism training. The results show that the students who are the subject of the research have the ability to become content creators, can produce videos, and understand journalistic work. The students carry out these three aspects based on the moral values of the pesantren. In addition, the students have the ability to read and understand digital media. One of the emphasis in digital literacy is on hoax news. As many as 75% of digital literacy participants stated that if they get news, they will check the truth. Uniquely, the santri emphasize the values and traditions of the pesantren in showing literate behavior. Thus, this study can contribute to the development of digital literacy based on Islamic boarding schools' values.***Pesantren dan madrasah memiliki tradisi sendiri dalam menerapkan literasi digital. Artikel ini bertujuan untuk menjawab bagaimana praktik literasi digital di pesantren Darunajah? Metode yang digunakan dalam kajian ini adalah metode partisipatif dengan melibatkan subjek penelitian dalam proses penelitian. Terdapat tiga treatment literasi digital yang diberikan kepada subjek yaitu pelatihan content creator, pelatihan pembuatan video, dan pelatihan jurnalistik Islam. Hasilnya menunjukkan bahwa santri yang menjadi subjek penelitian memiliki kemampuan untuk menjadi konten creator, dapat memproduksi video, dan memahami kerja jurnalistik. Para santri melakukan ketiga aspek tersebut berbasis pada nilai moral pesantren. Selain itu, para santri memiliki kemampuan membaca dan memahami media digital. Salah satu penekanan dalam literasi digital adalah tentang berita hoaks. Sebanyak 75% peserta literasi digital menyatakan bahwa jika mereka mendapatkan berita maka mereka akan mengecek kebenarannya. Uniknya para santri menekankan nilai-nilai dan tradisi pesantren dalam menunjukkan perilaku literate. Dengan demikian, studi ini dapat berkontribusi bagi pengembangan literasi digital yang berbasis pada nilai-nilai pesantren.